Membros: v. 10, n. 3 (2012) - ., .. (RENOTE, 2012)
Alessandra Pereira Rodrigues - Instituto Federal Sul Riograndense - Pelotas Alexandra Macedo - UFRGS Alexandre Ribeiro - UCS Ana Carolina B de Marchi - UPF Ana Marli Bulegon - UNIFRA Barbara Gorziza Avila - UFRGS Carla Valentini - UCS Carlos Tadeu Queiroz de Morais - PGIE - UFRGS Cleuza Maria Maximino Carvalho Alonso - UFSM Elisa Boff - UCS Eliseo Reategui - FACED/PGIE - UFRGS Evandro Alves - CINTED/UFRGS Gilse Antoninha Morgental Falkembach - UFSM/CINTED Janete Sander Costa - ULBRA Javier Díaz - Universidad de la Plata, Argentina Joice Otsuka - UFSCAR John A. Campell - Universidade de Londres - Inglaterra José Valdeni Lima - PGIE/UFRGS Liane Margarida Rockenbach Tarouco - CINTED/FACED/PGIE - UFRGS Liliana Passerino - FACED e PGIE/UFRGS Louise Jeanty de Seixas - Faculdade de Farmácia/UFRGS Magda Bercht - Instituto de Informática/PGIE - UFRGS Marcelo Augusto Rauh Schmitt - Instituto Federal do Rio Grande do Sul Marcelo Foohs - FACED /UFRGS Marcia Notare - Instituto de Matemática/UFRGS Marcus Vinícius de Azevedo Basso - Instituto de Matemática/UFRGS Maria Cristina Biazus - Instituto de Artes/UFRGS Maria Cristina Moraes – Informática / PUC-RS Marlise Geller - ULBRA Marina Nakayama - UFSC Michelle Denise Leonhardt - Departamento de Informática Aplicada/UFRGS Patrícia Alejandra Behar - FACED/PGIE - UFRGS Querte Mehlecke - FACCAT/RS Renato Dutra - Universidade Anhembi Morumbi Ricardo Azambuja Silveira - INF/UFSC Roberto dos Santos Rabello – UPF Roseclea Medina - UFSM Silvia Meirelles Leite - UFPEL Thaísa Müller – PGIE/UFRGS Teresa Chambel - Universidade de Lisboa - Portugal Valéria Costa – PGIE/UFRGS Coordenação : Liane Margarida Rockenbach Tarouco - CINTED/UFRGS Eliseo Reategui - PGIE/UFRGS José Valdeni Lima - PGIE/UFRGS